The Rijeka draft of a Convention on the liability of operators of nuclear ships : a very late requiem - Handrlica, Jakub (Array, 2020)
Sixty years ago, from 20th to 26th September 1959, the Nineteenth Conference of the International Maritime Committee (Comité Maritime International) was held in Rijeka. Facing the challenges arising from contemporary plans to use nuclear power in marine transport (in particular to use nuclear reactors as a source of transport for both civil and military ships), the Conference adopted a draft of a convention that aimed to address the issue of liability of the operators of nuclear ships. The draft convention reflected the fact that liability issues arising from nuclear ships considerably differ from those issues, arising from the operation of land-based nuclear reactors. This draft convention, which became later widely known as “the Rijeka Draft” in legal literature, provided for basic liability principles that were to be applied to operators of nuclear ships. The Rijeka Draft became crucial for the later developments in the field of international nuclear law, in particular for the adoption of the Brussels Convention on the Liability of Nuclear Ships at the Eleventh Session of the Diplomatic Conference on Maritime Law in 1962. However, it also influenced the content of several other bi-lateral agreements. The 60th anniversary of the Rijeka Draft allows a good opportunity to revisit the principles provided by the draft convention as well as to revisit the impact of this draft on further development of international nuclear law.